A Novel Promising Strain of Trichoderma evansii (WF-3) for Extracellular α-Galactosidase Production by Utilizing Different Carbon Sources under Optimized Culture Conditions. (13th July 2014) - Chauhan, Aishwarya; Siddiqi, Nikhat Jamal; Sharma, Bechan
Abstract : A potential fungal strain of Trichoderma sp. (WF-3) was isolated and selected for the production of α -galactosidase. Optimum conditions for mycelial growth and enzyme induction were determined. Basal media selected for the growth of fungal isolate containing different carbon sources like guar gum (GG), soya bean meal (SM), and wheat straw (WS) and combinations of these carbon substrates with basic sugars like galactose and sucrose were used to monitor their effects on α -galactosidase production. The results of this study indicated that galactose and sucrose enhanced the enzyme activity in guar gum (GG) and wheat straw (WS). Maximum α -galactosidase production (213.63 UmL −1 ) was obtained when the basic medium containing GG is supplemented with galactose (5 mg/mL). However, the presence of galactose and sucrose alone in the growth media shows no effect. Soya meal alone was able to support T. evansii to produce maximum enzyme activity (170.36 UmL −1 ). The incubation time, temperature, and pH for the maximum enzyme synthesis were found to be 120 h (5 days), 28°C, and 4.5–5.5, respectively. All the carbon sources tested exhibited maximum enzyme production at 10 mg/mL concentration. Among the metal ions tested, Hg was found to be the strongest inhibitor of the enzyme. Among the chelators, EDTA acted as stronger inhibitor than succinic acid.